A Book Review on Quan Manh Ha and Cab Tran’s (editors) _The Colors of April: Fiction on the Vietnam War’s Legacy 50 Years Later_ - Smith, Broderick (SARE: Southeast Asian Review of English, 2025)
Abstract The Colors of April, edited by Quan Manh Ha and Cab Tran, is a pioneering anthology that includes a range of short stories that amplifies the voices of Vietnamese and Vietnamese American authors. In recognition of the 50th anniversary of the conclusion of the Vietnam War (1975-2025), the book aims to challenge false conceptions of this war through the collection of multiple perspectives and stories that address how the war impacted different people, regardless of their political and militaristic affiliations. The major themes of this text include displacement, trauma, and transnational remembrance. This book also provides a broader understanding of war and seeks to highlight the political and ethical act of translational and multi-cultural literature—an act that demonstrates the humanity that is often forgotten in the turmoils of war.